2019
DOI: 10.1128/jvi.02154-18
|View full text |Cite
|
Sign up to set email alerts
|

Development of an ORF45-Derived Peptide To Inhibit the Sustained RSK Activation and Lytic Replication of Kaposi's Sarcoma-Associated Herpesvirus

Abstract: The lytic replication of Kaposi’s sarcoma-associated herpesvirus (KSHV) requires sustained extracellular signal-regulated kinase (ERK)-p90 ribosomal S6 kinase (RSK) activation, which is induced by an immediate early (IE) gene-encoded tegument protein called ORF45, to promote the late transcription and translation of viral lytic genes. An ORF45-null or single-point F66A mutation in ORF45 abolishes ORF45-RSK interaction and sustained ERK-RSK activation during lytic reactivation and subsequently results in a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…We further investigated whether KSHV gene expression was affected by RNF5 loss in BCBL1 cells. Approximately 5% of BCBL1 cells undergo ORF45-positive spontaneous lytic replication [ 39 ], low spontaneous expression of KSHV lytic genes was observed in BCBL1 cells, and the 12-O-tetradecanoylphorbol-13-acetate (TPA) treatment greatly induced lytic gene expression [ 40 ]. Both spontaneous and TPA-induced lytic gene expression levels of ORF45 and K8 were decreased in RNF5 KO BCBL1 cells compared with control cells ( Fig 1E ), whereas the latent gene expression level of LANA was not affected.…”
Section: Resultsmentioning
confidence: 99%
“…We further investigated whether KSHV gene expression was affected by RNF5 loss in BCBL1 cells. Approximately 5% of BCBL1 cells undergo ORF45-positive spontaneous lytic replication [ 39 ], low spontaneous expression of KSHV lytic genes was observed in BCBL1 cells, and the 12-O-tetradecanoylphorbol-13-acetate (TPA) treatment greatly induced lytic gene expression [ 40 ]. Both spontaneous and TPA-induced lytic gene expression levels of ORF45 and K8 were decreased in RNF5 KO BCBL1 cells compared with control cells ( Fig 1E ), whereas the latent gene expression level of LANA was not affected.…”
Section: Resultsmentioning
confidence: 99%
“…In KSHV, ORF36 is a substrate of ORF45-activated kinases and ORF45 enhances the kinase activity of ORF36; although untested, this may similarly occur for the MHV68 homologs. KSHV ORF45 causes sustained activation of p90 ribosomal kinases (RSKs) and extracellular regulated kinases (ERKs) (59)(60)(61)(62)(63)(64), and subsequent studies also identified that KSHV ORF45, ORF36, and RSK form a stable complex (57). Another function of KSHV ORF45 is suppression of interferon regulatory factor 7 (IRF7), a crucial regulator of type I interferon gene expression (78)(79)(80).…”
Section: Discussionmentioning
confidence: 99%
“…signaling KSHV ORF45 interacts with the cellular p90 ribosomal S6 kinase (RSK1/2) and forms a ternary complex with the extracellular signal-regulated kinase (ERK2) of the mitogen-activated protein kinase (MAPK) pathway, strongly stimulating their kinase activities (59)(60)(61)(62)(63)(64)(65). This correlates with sustained phosphorylation of RSK1/2 and ERK1/2, which are functional mediators of MAPK/ERK signaling, and are important for MHV68 lytic infection (66).…”
Section: Upregulation Of Rnapiii Activity By Mhv68 Orf45 Requires Sti...mentioning
confidence: 99%
“…BI-D1870, a RSK1/2 inhibitor, suppresses KSHV lytic gene expression and virus production. The RSK1/2 serine/threonine kinase is activated by its interaction with KSHV pORF45 and a small peptide blocking this interaction has been shown to inhibit viral lytic gene expression and viral progeny formation [133]. Furthermore, crizotinib, an inhibitor of ALK and c-Met, suppresses the growth of PEL cells in a mouse xenograft model [134].…”
Section: Kinase Inhibitorsmentioning
confidence: 99%